The Impact of Safety and Health Concerns on Environmental Attitudes towards Green Electronic Products among Lecturers - Iman Khalid, A. Qader; Yuserrie, Zainuddin (Research Academy of Social Sciences, 2013)
The purpose of this study is to contribute to the body of knowledge within the area of environmental attitudes towards green marketing. Therefore, this study intends to identify the influence of safety and health concerns on environmental attitude, towards lead-free electronic products (green electronics) amongst lecturers. In this study safety and health concerns is conceptualized as the consumer‘s concern for quality of life, health issues and the environment for humans and non-human species. Hence, through a self-administered questionnaire among 170 lecturers, from USM main campus and USM engineering campus the study found some revealing insights. Through the results of this study, safety and health concerns had a significant positive influence on lecturers‘ environmental attitude. The theory of planned behavior Azjen (1985) supported the findings of this study for safety and health concerns and environmental attitudes, which is related to behavioral beliefs part of the theory: The person‘s beliefs that the behavior leads to certain outcomes and his or her evaluations of these outcomes. Therefore, attitudes are determined by behavioral beliefs.